COMMUNITY ENGAGEMENT IN NATURAL DISASTER MANAGEMENT: A DECADE OF PRACTICE AND FUTURE DIRECTIONS IN INDONESIA - Azhar Firdaus; Tyas Ismi Trialfhianty; Deni Muhammad Nur Satrio; Andini Putri Riandani (Jurnal Kommunity Online, 2026)
As one of the most disaster-prone nations in the world, Indonesia confronts recurring geophysical and hydrometeorological hazards including earthquakes, tsunamis, volcanic eruptions, and seasonal floods. Over the ten-year period from 2014 to 2024, community engagement has become a foundational element of effective disaster risk reduction (DRR) policy and practice, marking a decisive transition away from top-down, state-centric governance toward participatory, culturally grounded, and technology-assisted approaches. This article presents a systematic review of the scholarly literature on community engagement in Indonesian natural disaster management, with comparative reference to peer nations in Southeast Asia, particularly the Philippines and Malaysia. Drawing on 63 sources retrieved from the Scopus database and screened through a PRISMA-informed protocol, the review synthesizes evidence across five thematic domains: culturally adapted communication strategies, community-based DRR programs, indigenous and local knowledge integration, the role of technology and social media, and the inclusion of gender and marginalized groups. Key findings indicate that Indonesia distinguishes itself through deep institutionalization of the gotong-royong (mutual cooperation) ethic within formal DRR programs, and through hybrid communication systems that combine indigenous signaling practices with digital platforms. Nonetheless, persistent implementation deficits remain in institutional coordination, sustainable financing, gender mainstreaming, and mental health integration. Comparative analysis demonstrates that, while all three Southeast Asian nations share collectivist cultural orientations favorable to community-based DRR, Indonesia exhibits a more systematic programmatic architecture through flagship initiatives such as Desa Tangguh Bencana (Destana) and the SISTER VILLAGE program. Emerging research priorities include hybrid digital-indigenous early warning systems, blockchain-enabled community risk financing, and participatory development of culturally sensitive psychosocial support frameworks.